A functional CNVR_3425.1 damping lincRNA FENDRR increases lifetime risk of lung cancer and COPD in Chinese. (23rd December 2017) - Yang, Lei; Wu, Di; Chen, Jinbin; Chen, Jiansong; Qiu, Fuman; Li, Yinyan; Liu, Li; Cao, Yi; Yang, Binyao; Zhou, Yifeng; Lu, Jiachun
Abstract : This is the first study to investigate on association between gCNVs in genomic imbalances and disease risk. We identified CNVR_3425.1 to be a risk indicator of lung cancer and COPD by repressing FENDRR, which can weaken transcriptional efficiency of FENDRR. Abstract: Genomic imbalance referring to somatic variation in chromosome copies represents the most frequent event in tumorigenesis. Germline copy number variations (gCNVs) overlapping regions of genomic imbalance harbor similar structural characteristics and thus influence tumor susceptibility. We aimed to test effects of such gCNVs on the risk of lung cancer and chronic obstructive pulmonary disease (COPD). Genomic imbalance of lung cancer was determined by the array comparative genomic hybridization (aCGH), and common gCNVs at these imbalance regions were genotyped in lung cancer-based and COPD-based retrospective studies. Functional assays were conducted to assess function of promising CNVs. A total of 115 genomic imbalances were discovered occurring at a frequency of more than 25%. The CNVR_3425.1, overlapping the chr16q24.1 with genomic imbalance, was significantly associated with increased risks of lung cancer (OR = 1.76; 95% CI = 1.46–2.11) and COPD (OR = 1.98; 95% CI = 1.57–2.51). The increase copy of CNVR_3425.1 forms a new additional truncated FOXF1 adjacent non-coding developmental regulatory RNA ( FENDRR ) sequences comparing the gene promoter and perturbs the transcriptional factors (TFs) binding to the original FENDRR promoter and further downregulates FENDRR, a long intergenic non-coding RNA (lincRNA) that functions to inhibit lung cancer by affecting expressions of an abundant number of genes, including the tumor suppressor FOXF1. FENDRR can upregulate FOXF1 by competitively binding to miR-424. The TFs early growth response 1 (EGR1) and transcription factor AP-2 alpha (TFAP2A) were further found to involve the CNVR_3425.1-mediated FENDRR dysregulation. These findings suggested the CNVR_3425.1 to be a possibly predictive biomarker for the risk of lung cancer and COPD, and targeted molecular therapy pertaining to FENDRR upregulation may be a valuable pathway to fight two diseases.